Focal Adhesion Kinase (FAK) Inhibition Synergizes with KRAS G12C Inhibitors in Treating Cancer through the Regulation of the FAK–YAP Signaling - Baoyuan Zhang; Yan Zhang; Jiangwei Zhang; Ping Liu; Bo Jiao; Zaiqi Wang; Ruibao Ren (Advanced Science, 2021)
Abstract KRAS mutation is one of the most prevalent genetic drivers of cancer development, yet KRAS mutations are until very recently considered undruggable. There are ongoing trials of drugs that target the KRAS G12C mutation, yet acquired drug resistance from the extended use has already become a major concern. Here, it is demonstrated that KRAS G12C inhibition induces sustained activation of focal adhesive kinase (FAK) and show that a combination therapy comprising KRAS G12C inhibition and a FAK inhibitor (IN10018) achieves synergistic anticancer effects. It can simultaneously reduce the extent of drug resistance. Diverse CDX and PDX models of KRAS G12C mutant cancer are examined and synergistic benefits from the combination therapy are consistently observed. Mechanistically, it is found that both aberrant FAK–YAP signaling and FAK‐related fibrogenesis impact on the development of KRAS G12C inhibitor resistance. This study thus illustrates the mechanism of resistance of cancer to the treatment of KRAS G12C inhibitor, as well as an innovative combination therapy to improve treatment outcomes for KRAS G12C mutant cancers.